Governmental claims system for marine ecological damage in China - Lei Yang; Hao Liang; Yu-jing Li (Frontiers in Marine Science)
The governmental claims system designed to address damage to China’s marine ecological environment faces several significant challenges. These challenges include ambiguities in the legal attributes of the system, disputes over the identity and role of claimants, the sequencing and interaction of consultation processes, the enforcement of environmental laws, the conditions and scope of the right to claim, and the legitimacy of consultative agreements. Such theoretical and practical disputes have hindered the effectiveness of the system. To enhance this system, it is crucial to establish a robust theoretical foundation for claims based on public law principles. Additionally, it is essential to explore the development of a centralized mechanism for managing claims related to marine ecological damage, particularly through administrative bodies responsible for marine ecological supervision. It is also critical to clarify the conditions under which claims can be initiated and to refine the procedural framework governing consultations. Furthermore, it is vital to strengthen the synergy between administrative law enforcement and consultation processes, while simultaneously fostering international cooperation in the marine ecosystem governance. The thesis delves into the nature of claim litigation as a distinct category of public interest litigation and elucidates the relationship with other types of legal proceedings.